Extracorporeal Membrane Oxygenation Use in Thoracic Surgery - Pavel Suk; Vladimír Šrámek; Ivan Čundrle (Membranes, 2021)
This narrative review is focused on the application of extracorporeal membrane oxygenation (ECMO) in thoracic surgery, exclusive of lung transplantation. Although the use of ECMO in this indication is still rare, it allows surgery to be performed in patients where conventional ventilation is not feasible—especially in single lung patients, sleeve lobectomy or pneumonectomy and tracheal or carinal reconstructions. Comparisons with other techniques, various ECMO configurations, the management of anticoagulation, anesthesia, hypoxemia during surgery and the use of ECMO in case of postoperative respiratory failure are reviewed and supported by two cases of perioperative ECMO use, and an overview of published case series.